These Little Ones - Edith Nesbit (Blackmask Online, 2009)
It had been a good day; lessons had been easier than usual, and teacher had read them a story of some naughty little boys who had thrown a dog into the water and aimed stones at it, and about a good little boy who had saved its life; and of how the dog had loved him ever after. Thus begins The Dog-Dream, one of the 10 stories in this poignant and sometimes bittersweet collection of tales about the tragedies of childhood. Some of the other Nesbit stories included are: The Criminal, The Ashpits, and Thor and the Hammer.